Manager's guide to contingency planning for disasters protecting vital facilities and critical operations - Myers, Kenneth N. 1932- (John Wiley & Sons, 1999)
Kenneth N. Myers, one of the world's foremost innovators in the field of disaster recovery and business continuity planning, now provides you with a time-tested contingency planning philosophy, an implementation strategy, and a plan development methodology that matches the low probability of a disaster with the need for low-cost solutions. While other books offer complex and detailed approaches that are difficult to understand and even more costly to implement, Manager's Guide to Contingency Planning for Disasters: Protecting Vital Facilities and Critical Operations presents an unusually straightforward format that deals in "what if" strategies instead of inordinately detailed procedures. It also emphasizes strategies to maintain business continuity, regardless of the cause of the disaster.